Culprit Lesion Morphology of Rapidly Progressive and Extensive Anterior-Wall ST-Segment Elevation Myocardial Infarction. (15th November 2022) - Okada, Kozo; Hibi, Kiyoshi; Kikuchi, Shinnosuke; Kirigaya, Hidekuni; Hanajima, Yohei; Sato, Ryosuke; Nakahashi, Hidefumi; Minamimoto, Yugo; Matsuzawa, Yasushi; Maejima, Nobuhiko; Iwahashi, Noriaki; Kosuge, Masami; et al.
Abstract : Background: Rapidly progressive, extensive myocardial injury/infarction (RPEMI) beyond the concept of wave-front phenomenon can be observed even when achieving timely reperfusion; however, the pathogenesis of RPEMI remains unknown. This retrospective study investigated clinical and lesion characteristics of RPEMI, focusing on culprit-lesion morphology (CLM). Methods: Among patients with extensive anterior-wall ST-segment elevation myocardial infarction due to proximal left anterior descending artery lesions who had reperfusion within 3 hours of symptom onset, 60 patients undergoing both intravascular ultrasound and cardiac magnetic resonance imaging were enrolled. Myocardial injury/infarction before reperfusion therapy was assessed by QRS scores at hospitalization electrocardiogram, and the extent of myocardial injury/infarction was evaluated by cardiac magnetic resonance imaging, which measured area at risk, infarct size, myocardial salvage index, microvascular obstruction, and left ventricular ejection fraction. RPEMI was defined as lower left ventricular ejection fraction (less median value) with microvascular obstruction. Results: Despite comparable onset-to-door and onset-to-reperfusion times and area at risk, patients with RPEMI showed higher QRS scores at hospitalization (5 [4.3–6] versus 3 [2–4], P <0.001) and infarct size (26.5±9.1 versus 20.4±10.5%, P =0.04), and a tendency toward lower myocardial salvage index (0.27±0.14 versus 0.36±0.20, P =0.10) compared with those without. Patients with versus without RPEMI more frequently observed specific CLM on intravascular ultrasound, characterized by the combination of vulnerable plaques, plaque ruptures, and/or large thrombi. When stratified by CLM-score composed of these 3 criteria, higher CLM-scores were or tended to be associated with higher QRS scores and incidence of RPEMI. In multivariate analyses including no-reflow phenomenon and final coronary-flow deterioration, increased CLM-score (≥2) was independently associated with high QRS scores and RPEMI (odd ratio 11.25 [95% CI, 2.43–52.00]; P =0.002). Conclusions: Vulnerable CLM was a consistent determinant of advanced myocardial injury/infarction both before and after reperfusion therapy and may play a pivotal role in the development of RPEMI.